CREATIVE ECONOMY BASED ON SYARIAH AS AN EFFORT TO INCREASE COMMUNITIES WELFARE: Case Study at BAPPEDA, East Java Province, 2019 - Syamsuri Syamsuri; Muhammad Reno Fathur Rahman (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2019)
Abstract: This study aims to analyze the government’s creative economic strategy in improving the welfare of the community, especially in the BAPPEDA of East Java Province and also to find out the efforts of regional governments in developing a sharia-based creative economy. Descriptive qualitative research methods are used by the author as an approach in this study. Data collection techniques are by documentation, interviews and observation. The results of the study indicate that the government’s creative economic strategies are established by building synergy with pentahelix elements, motivating innovation, realizing the “smart economy” program, and collaboration with BEKRAF. It also explained that the efforts of the regional government in developing a sharia-based creative economy are by producing halal products and involving syaria institutions into pentahelix elements and implementing the concept of mashlahah in creative economic activities.Abstrak: Ekonomi Kreatif Syariah Sebagai Upaya Peningkatan Ekonomi Umat. Penelitian ini bertujuan menganalisis strategi ekonomi kreatif pemerintah dalam meningkatkan kesejahteraan masyarakat, terutama di BAPPEDA Provinsi Jawa Timur, dan bagaimana upaya pemerintah daerah mengembangkan ekonomi kreatif berbasis syariah. Metode penelitian ini adalah kualitatif deskriptif dengan teknik pengumpulan data dokumentasi, wawancara, dan observasi. Hasil penelitian menunjukkan bahwa strategi ekonomi kreatif pemerintah dilakukan dengan bersinergi dengan elemen pentahelix, motivasi semangat dan inovasi, sadar program “smart economy”, dan kerjasama dengan BEKRAF. Hasil penelitian juga menjelaskan bahwa upaya pemerintah daerah dalam mengembangkan ekonomi kreatif berbasis syariah adalah dengan menghasilkan produk-produk ekonomi kreatif yang halal dan syar‘i, melibatkan institusi syariah ke dalam elemen pentahelix, dan menerapkan konsep mashlahah dalam kegiatan ekonomi kreatif.Kata Kunci: Ekonomi kreatif, kesejahteraan, ekonomi kreatif syariah